Uriah Tracy correspondence - Tracy, Uriah, 1755-1807.
ALS written by Tracy to Jonathan Dayton commenting on the readiness of Connecticut citizens for military service and on Federalist politics.
U.S. senator and representative from Connecticut and army officer. Used pseudonym Scipio.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Dayton, Jonathan, -- 1760-1824 -- Correspondence; Federal Party (U.S.); Military readiness; Connecticut -- Politics and government -- 1775-1865.; United States -- Politics and government -- 1797-1801.; Army officers; Public officials -- Connecticut; Representatives, U.S. Congress -- Connecticut; Senators, U.S. Congress -- Connecticut